Prohibitin viral gene transfer protects hippocampal CA1 neurons from ischemia and ameliorates post-ischemic hippocampal dysfunction - Kurinami, Hitomi (2014)
BACKGROUND AND PURPOSE: Prohibitin (PHB) is a multi-functional protein involved in numerous cellular activities. PHB overexpression protects neurons from injury in vitro, but it is unclear whether PHB can protect selectively vulnerable hippocampal CA1 neurons in a clinically relevant injury model in vivo and, if so, whether the salvaged neurons remain functional. METHODS: A mouse model of transient forebrain ischemia that mimics the brain damage produced by cardiac arrest in humans was used to test whether PHB expression protects CA1 neurons from injury. PHB-expressing viral vector was microinjected in mouse hippocampus to upregulate PHB. RESULTS: PHB overexpression protected CA1 neurons from transient forebrain ischemia. The protection was associated with dampened post-ischemic ROS generation, reduced mitochondrial cytochrome c release and decreased caspase-3 activation. Importantly, the improvement in CA1 neuronal viability translated into an improvement in hippocampal function: PHB expression ameliorated the spatial memory deficit induced by ischemia, assessed by the Y-maze test, and restored post-ischemic synaptic plasticity assessed by long-term potentiation, indicating that the neurons spared form ischemic damage were functionally competent. CONCLUSIONS: These data demonstrate that PHB overexpression protects highly vulnerable CA1 neurons from ischemic injury in vivo, and suggest that the effect is mediated by reduction of post-ischemic ROS generation and preservation of mitochondrial outer membrane integrity that prevents activation of apoptosis. Measures to enhance PHB expression could have translational value in ischemic brain injury and, possibly, other forms of brain injury associated with mitochondrial dysfunction.